EXTH-71. IND-ENABLING CHARACTERIZATION OF ONC206 AS THE NEXT BITOPIC DRD2 ANTAGONIST FOR NEURO-ONCOLOGY. (11th November 2019) - Prabhu, Varun; Rahman Kawakibi, Abed; Madhukar, Neel; Garnett, Mathew; McDermott, Ultan; Benes, Cyril; Wechsler-Reya, Robert; Elemento, Olivier; Stogniew, Martin; Oster, Wolfgang; DeMorrow, Sharon; Allen, Joshua
Abstract: ONC201 is the first clinical bitopic antagonist of DRD2, an oncogenic receptor in brain and neuroendocrine tumors. ONC206, a derivative of ONC201 that shares the imipridone core structure, is also a bitopic DRD2 antagonist that exhibits enhanced non-competitive effects, high specificity, nanomolar potency, and disruption of DRD2 homodimers. Broad nanomolar efficacy of ONC206 (GI50 < 78-889nM, CellTitre-Glo, 72h) was observed in >1, 000 GDSC cancer cell lines. Maximal ONC206 sensitivity was observed in pheochromocytoma, high-grade gliomas, neuroblastoma, medulloblastoma, sarcoma and cholangiocarcinoma cell lines exhibiting a DRD2+/DRD5- RNA expression signature. An exposure time of 48h at nanomolar concentrations was sufficient for maximal inhibition of tumor cell viability. ONC206 reduced the viability of normal human fibroblasts at higher doses (GI50 > 5µM), suggesting a wide therapeutic window. Antitumor efficacy without body weight loss was observed with 50 mg/kg weekly oral ONC206 in a dopamine-secreting HuCCT1 cholangiocarcinoma subcutaneous xenograft model. Biodistribution studies in Sprague-Dawley rats revealed a ~12 µM plasma Cmax with a systemic terminal half-life of ~6 hours upon a single oral dose of 50 mg/kg. Additionally, 5–10 fold higher ONC206 concentrations were observed in adrenal gland, bile duct, brain and bone marrow relative to plasma. Nanomolar concentrations were also observed in the CSF above DRD2 antagonism thresholds, unlike ONC201. GLP toxicology studies with weekly oral ONC206 in Sprague-Dawley rats and beagle dogs revealed no dose-limiting toxicities. Mild and reversible decreased body weight and/or body weight gain with no effects on food consumption were observed at the highest evaluated dose in both species. The highest non-severely toxic dose (HNSTD) was ≥ 16.7 mg/kg in dogs and ≥ 50 mg/kg in rats that exceeds efficacious doses in preclinical models. Using standard allometric scaling, a 90 mg starting dose of ONC206 was selected for the first-in-human clinical trial in biomarker-defined adult recurrent CNS tumors.